(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Among the many fields of foreseeable application of artificial intelligence, warfare must certainly be included. Operational and economic considerations argue in favor of algorithmic decision-making in said context. This raises a vast number of questions, both ethical and legal, peculiarly relevant to lethal autonomous weapons systems, defined as weapons that can select and engage their targets without human intervention, once activated. This contribution aims to illustrate and address the questions raised by such weapons, ranging from compliance with international humanitarian law to accountability and human dignity, and argues that human control over autonomous weapons can and must be retained.